Diretrizes para desbaste de Pinus taeda L. em função da altura dominante - Padoin, Veridiana (2007)
The study uses dominant trees to describe the tinning, because they are those that possess larger energy inside of a forest settlement. The main objective of the work is to model and to select models to describe the relationship among the potential number of trees for hectare in function of the dominant height, elaborating a system of curves guides how to aid in the determination of the tinning. The municipal and districts where are located the forests are: Cambará do Sul (RS), São Francisco de Paula (RS), Distrito de Tainhas (RS), Distrito dos Kroeff (RS), Bocaína do Sul (SC), Correia Pinto (SC), Curitibanos (SC), Lages (SC), Otacílio Costa (SC), Ponte Alta do Norte (SC) and Santa Cecília (SC). The units temporary sample random were installed using the Method of modified Prodan, or be, 12 trees were measured by unit sample being the center of the unit the dominant tree of the sample. The units were installed at forests in competition from 5 to 40 meters of dominant height. In those units they were measured: the distance of the 11 trees to the central dominant tree; diameter and the height of the 12 trees; the crown diameter, the length of total crown and the exposed crown length to the light of the 2 dominant trees of the sample. The calculated variables were the number of potential trees for hectare, the Index of relative spacing, the crown percentage and the index of competition of Glover and Hool. The modelling made calculations by the statistical package (Statistical Analysis System) version 8.0 and the adjustment of the equations and covariance analysis for the procedure GLM ( General Lineal Models). The equations that best describes the potential number of trees for hectare were Ln(Np) = 10,31285 - 1,28518*(ln(hdom) with a R²aj 0,68 and CV of 4,76% for the class of S'% of 14-20% and Ln(Np) = 10,36304 - 1,16938*(ln(hdom) with a R²aj 0,34 and CV of 5,24% for the class of S'% of 14-20%. The use of the dominant height as independent variable is efficient to describe the guidelines for tinning in the settlements of Pinus taeda. The model of negative exponential regression adjusts with good precision and low mistake the relationship among the potential number of trees for hectare and the dominant height. The variation of the values of potential frequency for hectare for a given dominant height is strongly reduced with the bedding of the data in classes of Index of relative spacing of Hart Becking larger than 14% and smaller than 14% allowing to elaborate frequency curves for hectare for those two situations. The development of the frequency curves stratified by Index of relative spacing influences in the dimension of the diameter of the trees for a same dominant height.